2019
DOI: 10.1016/s2214-109x(19)30328-6
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of sickle cell disease in children recruited in infancy in Kilifi, Kenya: a prospective cohort study

Abstract: Background Sickle cell disease is the most common severe monogenic disorder in humans. In Africa, 50-90% of children born with sickle cell disease die before they reach their fifth birthday. In this study, we aimed to describe the comparative incidence of specific clinical outcomes among children aged between birth and 5 years with and without sickle cell disease, who were resident within the Kilifi area of Kenya. Methods This prospective cohort study was done on members of the Kilifi Genetic Birth Cohort Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
66
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 36 publications
7
66
0
1
Order By: Relevance
“…The mean Hb level of sickle children in our study (8.04 gm/dL, SD 1.65) was similar to that found in a multi-country (Mali, Senegal, Cameroon, Gabon, and the Ivory Coast) analysis [38], and in studies from Ghana [35] and Brazil [23]; but higher than that of Kenyan cohorts [36,39]. We captured a signi cant mediating role of Hb in SCD-nutritional status association.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The mean Hb level of sickle children in our study (8.04 gm/dL, SD 1.65) was similar to that found in a multi-country (Mali, Senegal, Cameroon, Gabon, and the Ivory Coast) analysis [38], and in studies from Ghana [35] and Brazil [23]; but higher than that of Kenyan cohorts [36,39]. We captured a signi cant mediating role of Hb in SCD-nutritional status association.…”
Section: Discussionsupporting
confidence: 85%
“…This is appreciably lower than mean HAZ from children with SCD in Ilesa, Nigeria (− 0.52, SD 1.33) [18]; Enugu, Nigeria (− 0.50, SD 1.57) [34]; Ghana (− 0.86, SD 1.40) [35]; and Kenya (-1•10, SD 1•00) [36]. However, in the Kenyan SCD cohort (n = 128) with median age of 21.1 months, mean HAZ and WAZ did not signi cantly differ from those of non-sickle cell children [36]. No signi cant difference in mean HAZ was reported also in the study from Enugu, Nigeria [34] [37].…”
Section: Discussionmentioning
confidence: 73%
“…A consequence of improved child survival of homozygotes (SS genotype) also means that these children will reach school age but remain in stable, anaemic states. 11 SAC should not be neglected as targets for interventions aimed at reducing the anaemia burden. They remain at risk and can be targeted with specific interventions aimed at reducing parasitic infections, as well as supportive iron supplementation and the practical combination of interventions within the school environment.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Although SCD patients with alpha thalassaemia have a decreased admission rate, they have no survival advantage. 12 Several studies have shown the direct protective effects among SCD patients of HbF for painful episodes, leg ulcer, splenic sequestration and function, and retinopathy. 3,13,14 Genetic variations at three principal loci, BCL11A, HBS1L-MYB and HBB, on chromosomes 2, 6 and 11 respectively, and the various b s haplotypes, account for variable expression of HbF among different SCD populations through which the SCD phenotype is modified.…”
mentioning
confidence: 99%
“…34 To further corroborate their findings, severe anaemia was the most common reason for admission among a cohort of Kenyan children with SCD who were followed longitudinally for five years. 12 Furthermore, severe anaemia was associated with increased rates of pain crisis, cognitive impairment, and infections among children with SCD in the USA. 35 Also, their findings indicate that, rather than relying solely on medical procedures, policies geared towards improvement in the socioeconomic status of people living in developing countries may mitigate some SCD complications.…”
mentioning
confidence: 99%